Epidemiology, natural history, and outcome of chronic hepatitis B in children - Chenyang Huang; Jing Li; Min Zhang; Junliang Fu; Fu-Sheng Wang; Haijuan Wang (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Hepatitis B virus (HBV) infection is a global epidemic whose prevention and control among children warrant significant attention. Despite the availability of effective vaccines, the disease continues to affect millions of children worldwide, underscoring the need for a comprehensive understanding of its epidemiology and natural history in this vulnerable population. While research on HBV in adults has advanced considerably, the natural history of HBV infection in children remains less well-defined and may differ from adult studies due to unique immunological and physiological characteristics. This article reviews the epidemiological characteristics of HBV infection in children worldwide and summarizes the research progress on the natural outcomes of children with chronic HBV infection. Furthermore, the necessity of this review stems from the critical role that early detection, monitoring, and timely intervention play in mitigating the long-term consequences of chronic hepatitis B (CHB) in children. By synthesizing current evidence and identifying knowledge gaps, we hope to inform clinical practice, guide future research directions, and ultimately improve the health outcomes of children living with HBV. In doing so, this review article offers a valuable reference for healthcare providers, researchers, and policymakers working to combat the global challenge of HBV infection among children. The aim is to provide a relevant reference for the monitoring, screening, diagnosis, and treatment of children with CHB.